2021
DOI: 10.1590/1982-3703003201165
|View full text |Cite
|
Sign up to set email alerts
|

Mulheres em Espera pela Adoção: Sentimentos Apresentados nas Diferentes Etapas Desse Processo

Abstract: Resumo Este estudo tem o objetivo de compreender quais os sentimentos relatados por mulheres na espera pela adoção em dois diferentes momentos: na espera durante o processo de habilitação à adoção e na fila do Sistema Nacional de Adoção e Acolhimento (SNA). Esses anseios têm sido descritos na literatura de forma pouco específica no que diz respeito às etapas do processo de adoção, ainda que mulheres em espera pela adoção experimentem emoções singulares devido à indeterminação temporal em sua transição para a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…A large part of the studies highlighted the importance of intervening in the initial adaptation period of adoptive families, which meets national investigations on adoption (Resmini, 2018;Schwochow & Frizzo, 2021;Silva, 2018). The results of these studies showed improvements in parenting skills, changes related to greater attachment security, change in children's symptoms/behaviors, as well as less stress and improvement in parental mental health.…”
Section: Final Considerationsmentioning
confidence: 92%
“…A large part of the studies highlighted the importance of intervening in the initial adaptation period of adoptive families, which meets national investigations on adoption (Resmini, 2018;Schwochow & Frizzo, 2021;Silva, 2018). The results of these studies showed improvements in parenting skills, changes related to greater attachment security, change in children's symptoms/behaviors, as well as less stress and improvement in parental mental health.…”
Section: Final Considerationsmentioning
confidence: 92%